Agreement of iCare IC200 tonometry with Perkins applanation tonometry in healthy children - Stoddard-Bennett, Theo; Jackson, Nicholas J.; Robbins, Laura; Villanueva, Phillip; Suh, Soh Youn; Demer, Joseph L.; Pineles, Stacy L.; Fung, Simon S.M. (Journal of AAPOS, 2022)
To assess interdevice agreement between the iCare IC200 rebound tonometer and Perkins applanation tonometry (gold standard) in a healthy pediatric population. A total of 42 eyes of 42 healthy children were assessed using both tonometers. Data was collected on subject’s age, sex, best-corrected visual acuity, and central corneal thickness (CCT). Intraclass correlation coefficient (ICC) and Bland-Altman analyses were used to determine agreement between IC200 and Perkins applanation tonometers. Linear regression analyzed the effects of intraocular pressure (IOP) on device difference. The mean age and standard deviation of healthy pediatric subjects was 10.0 ± 3.3 years. The mean difference between IC200 and Perkins tonometers (IC200-Perkins) was 0.72 mm Hg, with a mean of 17.1 ± 3.0 mm Hg and 16.4 ± 2.5 mm Hg, respectively. The absolute agreement, or ICC, between tonometers was 0.63 (95% CI, 0.56-0.70). Bland-Altman analysis showed 95% limits of agreement ranging from −5.2 to +6.6 mm Hg. CCT was not correlated with IOP for either the IC200 (P = 0.35) or the Perkins tonometer (P = 0.052). Compared to applanation tonometry, IC200 overestimated IOP in healthy children, with a greater frequency of readings > +2 mm Hg than < −2 mm Hg compared to Perkins. There was moderate agreement between tonometers. CCT was not found to influence IOP measurement for either tonometer.